Access to Knowledge in the Digital Age: Unlocking Kyrgyzstan’s Collections - Bekbalaeva, Jyldyz (ADA University Library, 2024)
In Kyrgyzstan, libraries have gone through multiple transformations reflecting political, economic and societal changes since the country gained independence. Libraries look to expand the professional network through making the country’s resources available to researchers and academics locally and globally. Multiple digitization projects have been implemented; however, the accessibility and discoverability issues remain and majority of collections are yet not accessible to the public even when converted into digital format. While this presents the technological issue, the cultural aspect also imposes challenges event to a greater extent. The paper examines the access to rare heritage collections in Kyrgyzstan based on the example of the Museum of Rare Books of the Issyk-Kul Oblast Library, located in the eastern part of the country.
Keywords: Heritage collections; Kyrgyzstan; Rare books